Breaking barriers with translation: contextualization in curriculum design for global education - Glenda Erica Niles (Quality Education for All)
Purpose – This paper aims to highlight how translation can be used to contextualize curriculum materials, ensuring cultural relevance and accessibility for students in low- and middle-income countries. The research problem addressed is the lack of accessible and relevant educational resources for diverse cultural and linguistic backgrounds, hindering effective learning experiences. Design/methodology/approach – The paper discusses the importance of translation and contextualization in curriculum design for global education, focusing on the case of the STEM Teacher/student Education for Primary Schools project, which was aimed at improving STEM primary school education in Benin, Cameroon and the Democratic Republic of Congo. Findings – Results show that using translation as a form of contextualization successfully bridges global education with localization, providing culturally responsive science textbooks and enhancing teacher professional development. Practical implications – The implications include promoting student success, enhancing scientific learning outcomes and fostering critical thinking and creativity among students. Originality/value – Translation in curriculum design should not be overlooked as a way to expose students in LMICs and other languages to high-quality materials available in higher-income, English-speaking countries. For policymakers and curriculum developers, translation provides the route through which a country’s STEM curriculum can be contextualized to provide culturally relevant and meaningful educational resources for all students.